Purification and Characterization of Thermostable Chitinase from Bacillus SW41 for Chitin Oligomer Production - Wahyuni, S.; Suhartono, M.T.; Khaeruni, A.; Purnomo, A.S.; Asranudin; Holilah; Riupassa, P.A. (Asian Journal of Chemistry, 2016)
Bacillus SW41 was isolated from water of shrimp ponds in Maros, South Sulawesi, Indonesia. Molecular identification showed that the isolate belongs to Bacillus group, strains SW41. A chitinase produced by Bacillus SW41 was purified and characterized. The extracellular enzyme was isolated by successive hydrophobic interaction and gel filtration chromatography. The enzyme was shown to have a relative high molecular weight of 130.2 kDa by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Through the stages of purification, chitinase could be purified 8.1 fold. Chitinase SW41 showed optimum activity at pH 4 and stable at 60-70 °C. As a thermostable enzyme, chitinase SW41 showed t1/2 relatively long 8.8 h and 8.25 h at 60 and 70 °C, respectively. Another unique feature of chitinase SW41 was indicated on the hydrolysis of colloidal chitin and the ability to produce (GlcNAc)-(GlcNAc)5 through HPLC analysis.